“The Bearers of Unholy Potential”: Confessing Church Sermons on the Jews and Judaism - Skiles, William (Studies in Christian-Jewish Relations, 2016)
This article examines the nature and frequency of comments about Jews and Judaism in sermons delivered by Confessing Church pastors in the Nazi dictatorship. The approach of most historians has focused on the history of antisemitism in the German Protestant tradition—in the works, pronouncements, and policies of the German churches and its leading figures. Yet historians have left unexamined the most elemental task of the pastor—that is, preaching from the pulpit to the German people. What would the average German congregant have heard from his pastor about the Jews and Judaism on any given Sunday? I searched German archives, libraries, and used book stores, and analyzed 910 sermon manuscripts that were produced and disseminated in the Nazi regime. I argue that these sermons provide mixed messages about Jews and Judaism. While on the one hand, the sermons express admiration for Judaism as a foundation for Christianity, an insistence on the usage of the Hebrew Bible in the German churches, and the conviction that the Jews are spiritual cousins of Christians. On the other hand, the sermons express religious prejudice in the form of anti-Judaic tropes that corroborated the Nazi ideology that portrayed Jews and Judaism as inferior: for instance, that Judaism is an antiquated religion of works rather than grace; that the Jews killed Christ and have been punished throughout history as a consequence. Furthermore, I demonstrate that Confessing Church pastors commonly expressed anti-Judaic statements in the process of criticizing the Nazi regime, its leadership, and its policies.